Wondering how others interpret it: Social value of public information - Alia Gizatulina (Max Planck Institute for Research on Collective Goods, 2013)
This paper studies the social value of public information in environments without common knowledge of the data-generating process. We show that the stronger the coordination motive behind agents' behaviour is, the more they use private or public signals in the way that they suspect others are doing it. Consequently, the negative impact of public communication noted by Morris and Shin (2002) can be amplified if agents suspect that others take the public signal too literally and/or are too inattentive to their private signals. Social welfare, if measured as in Morris and Shin (2002), always increases in the precision of the public signal when each agent evaluates its precision correctly, but believes that others did not understand the public signal at all, which suggests that there is a scope to obliterate public communication in a specific way, by making it, e.g., sophisticated and technical. By contrast, measuring welfare as in Woodford (2005) reverses, in general, desirability for such obliteration and non-commonality of signals' understanding.
Keywords: D82; E58; 330; transparency; central bank communication; common p-belief; coordination game; higher-order uncertainty